1993
DOI: 10.1002/humu.1380020507
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening of Japanese patients with gaucher disease: Phenotypic variability in the same genotypes

Abstract: Gaucher disease is the most prevalent sphingolipidosis, characterized by genetic deficiency of lysosomal hydrolase glucocerebrosidase, and is inherited in an autosomal recessive manner. To characterize the molecular basis of Gaucher disease in Japan, we analyzed for the presence of the two known mutations (1448C and 754A) in the glucocerebrosidase gene of 15 patients (14 families) with Gaucher disease by selective amplification and restriction endonuclease analysis. We found that the 1448C and 754A mutations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In conclusion, our results emphasize the role of this relatively rare mutation in determining Gaucher disease; the presence in three different compound heterozygotes further explains the genotype/phenotype correlation (Theophilus et al 1989b, Zimran et al 1989, Kawame et al 1993, Sibille et al 1993, Sidransky et al 1994.…”
Section: Discussionsupporting
confidence: 73%
“…In conclusion, our results emphasize the role of this relatively rare mutation in determining Gaucher disease; the presence in three different compound heterozygotes further explains the genotype/phenotype correlation (Theophilus et al 1989b, Zimran et al 1989, Kawame et al 1993, Sibille et al 1993, Sidransky et al 1994.…”
Section: Discussionsupporting
confidence: 73%
“…For example, one group has shown that mutations N370S, L444P, c.84-85insG, and IVS2ϩ1GrA account for 196% of the mutated alleles in Ashkenazi Jewish patients, although they constitute !75% of the mutated alleles in non-Jews (Beutler et al 1992;Beutler and Gelbart 1993). Among Japanese patients with Gaucher disease, neither mutation N370S nor c.84-85insG are seen, but L444P and F213I are relatively common, lending further support to the founder-effect theory (Kawame et al 1993;Eto and Ida 1999). In the Portuguese Gaucher population, the N370S mutation accounts for 63% of the mutated alleles, and two other rare mutations, G377S and N396T, are commonly encountered (Amaral et al 1993;Amaral et al 1999).…”
Section: Analysis and Classification Of 304 Mutant Alleles In Patientmentioning
confidence: 85%
“…The procedures were based on the approach used for Gaucher's disease. 3,17 The primers used for the 754A mutation were 5'-GACTGGCAAGTGATAAGC-3' (sense) and 5'-GGTTACAGTGAGTGAAGA-3' (antisense). The PCR fragment was purified with the Geneclean II kit (Bio 101, La Jolla, California, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%